Formation of reentrant circuits in the mid-myocardial infarct border zone. (1st April 2016) - Ciaccio, Edward J.; Coromilas, James; Wit, Andrew L.; Peters, Nicholas S.; Garan, Hasan
Abstract: Introduction: In this study, the mechanisms for onset and maintenance of mid-myocardial (intramural) reentrant circuits are considered, based upon anatomical structure. Method: A model of electrical activation wavefront curvature in the mid-myocardial postinfarction border zone is developed. Two arrhythmogenic structures are considered: 1. a constrained slab of viable tissue, and 2. a strand of surviving myocardial fibers with distal expansion. Equations are formulated to estimate activation coupling intervals, and ranges in taper and circuit dimensions, that will support functional conduction block during premature stimulation and reentrant ventricular tachycardia. Results: For onset and maintenance of reentry, the arrhythmogenic regions forming both slab and strand circuits are in the range of 50–600 µm at their thinnest dimension. For constrained slabs, unidirectional block leading to reentry forms in the thin-to-thick direction during premature stimulation, and functional block at lateral boundaries enable formation of a double-loop circuit. The activation wavefront proceeds around the impediment and then curves in the opposite direction through the slab, reentering the previously excited tissue. For strands, unidirectional block forms at a distal expansion in response to premature stimulation. The strand reentrant circuit is bounded by infarcted tissue causing anatomical block, and can be single-loop or coaxial. For all architectures, circuit dimensions ranging from 1.6×1.6 mm to 3.5×3.5 mm support functional block when premature stimulus coupling intervals are 117–150 ms and ventricular tachycardia cycle lengths are 160–350 ms. Conclusions: For slab and strand mid-myocardial arrhythmogenic structures, taper and circuit dimensions govern ranges in premature excitation coupling intervals and tachycardia cycle lengths necessary to support functional block. Highlights: Ventricular tachycardia is commonly caused by a reentrant circuit. Reentrant circuits are not always mappable on endocardial or epicardial surfaces. In the study, a model is presented of mid-myocardial reentrant tachycardia. The model is based on convex wavefront curvature, which causes functional block. Both slabs and conduits of surviving viable mid-myocardial tissue can support reentry.